Predicting IVF outcome in poor ovarian responders - Oshrit Lebovitz; Jigal Haas; Nitzan Mor; Eran Zilberberg; Adva Aizer; Michal Kirshenbaum; Raoul Orvieto; Ravit Nahum (BMC, 2022)
Abstract Background Poor responders to ovarian stimulation are one of the most challenging populations to treat. As a failed cycle can cause a considerable emotional and economical loss, adequate fertility counseling addressing patients' expectations are highly important when facing patients with poor ovarian response. The study aimed to evaluate reproductive outcomes and to identify factors associated with live birth (LB) after fresh autologous IVF/intracytoplasmic sperm injection (ICSI) cycles of patients fulfilling the Bologna criteria for poor ovarian response (POR). Methods A retrospective study included 751 IVF/ICSI treatment cycles which yielded up to three retrieved oocytes, at a tertiary referral hospital between January 2016 and February 2020. A logistic regression analysis was used to adjust for confounders. Results Clinical pregnancy and LB rate per cycle were significantly higher among women younger versus older than 40 years (9.8% and 6.8% vs 4.5% and 2.1%, p < 0.01, respectively). Patients who achieved LB were significantly younger, had higher number of oocytes retrieved, fertilization rate and top-quality embryos (p < 0.05). Multivariable regression analysis identified patient's age (OR 0.90; 95% CI 0.845-0.97; p = 0.005) and mean number retrieved oocytes (OR 1.95; 95% CI 1.20-3.16; p = 0.007) as factors significantly associated with the probability of a LB. Conclusions The woman's age and the number of retrieved oocytes are both independent predicting factors of live birth in poor ovarian responders. Considering the risks, the high financial investment and poor reproductive outcomes involved in IVF treatments, raises questions regarding the adequacy of providing treatments in these patients' population. POR younger than 40 years may represent a possible exception due to acceptable probability for a LB.